WP2: Genetic innovation, seed systems and agrobiodiversity conservation for climate resilient food and nutrition security - Baum, Michael; Bishaw, Zewdie; Sánchez Garcia, Miguel; Amri, Ahmed; Yigezu, Yigezu Atnafe; Niane, Abdoul Aziz; Mdivani, Rusudan; Abay, Kibrom A. (International Center for Agricultural Research in the Dry Areas, 2022)
From Fragility to Resilience in Central and West Asia and North Africa (F2R-CWANA) WP2: Genetic innovation, seed systems and agrobiodiversity conservation for climate resilient food and nutrition security Inception Workshop – Morocco May 17, 2022